Chryseobacterium antibioticum sp. nov. with antimicrobial activity against Gram-negative bacteria, isolated from Arctic soil - Dahal, Ram Hari; Chaudhary, Dhiraj Kumar; Kim, Dong-Uk; Pandey, Ramesh Prasad; Kim, Jaisoo (Journal of antibiotics, 2021)
A yellow-pigmented, non-motile, Gram-stain-negative, pleomorphic bacterium, designated RP-3-3 T was obtained from soil sampled at the Arctic region in Cambridge Bay, NU, Canada. The strain is strictly aerobic, psychrotolerant, grow optimally at 15–20 °C and produces flexirubin type pigments. The strain is able to hydrolyse CM-cellulose, casein, starch and DNA. Strain RP-3-3 T showed antimicrobial activity against Gram-negative pathogens. A phylogenetic analysis based on its 16S rRNA gene sequence revealed that strain RP-3-3 T formed a lineage within the family Weeksellaceae and clustered as members of the genus Chryseobacterium . The closest members were Chryseobacterium shigense DSM 17126 T (98.7% sequence similarity), Chryseobacterium carnipullorum DSM 25581 T (98.7%) and Chryseobacterium oncorhychi 701B-08 T (98%). The genome is 4,910,468 bp long with 73 scaffolds and 4300 protein-coding genes. The anti-SMASH analysis of whole genome showed ten putative biosynthetic gene clusters responsible for various secondary metabolites. The sole respiratory quinone is MK-6. The major cellular fatty acids are iso-C 15:0 , iso-C 17:1 ω 9 c , iso-C 17:0 3-OH, summed feature 3 (iso-C 15 :0 2-OH/C 16 :1 ω 7 c ) and anteiso-C 15:0 . The major polar lipid is phosphatidylethanolamine. The DNA G + C content of the type strain is 36.9 mol%. In addition, the average nucleotide identity and in silico DNA–DNA hybridization  relatedness values between strain RP-3-3 T and phylogenetically closest members are below the threshold value for species delineation. Based on genomic, chemotaxonomic, phenotypic and phylogenetic analyses, strain RP-3-3 T represents novel species in the genus Chryseobacterium , for which the name Chryseobacterium antibioticum sp. nov. is proposed. The type strain is RP-3-3 T (=KACC 21620 T = NBRC 114360 T ).